ECONOMETRIC: FACTORS AFFECTING UNEMPLOYMENT IN SUMATERA PROVINCE - Arismaya, Anisa Dewi (Among Makarti, 2023)
ABSTRACTEconomic growth in a country can be hampered due to several factors, including increasing unemployment and poverty in Indonesia. This study aimed to analyze the factors that cause unemployment in Sumatra using a panel data regression model. The results of the panel data regression show that the minimum wage variable has a positive effect on unemployment in Sumatra, the economic growth variable has a negative effect on unemployment in Sumatra, and the population variable has a positive effect on unemployment in Sumatra. The high unemployment rate in a country will cause many problems, including increasing crime. Therefore, it requires attention from the government to equip the high population with counseling, education, coaching, and job training to increase the productivity of its people.ABSTRAKPertumbuhan ekonomi di sebuah negara dapat terhambat dikarenakan beberapa faktor antara lain karena meningkatnya pengangguran dan kemiskinan di Indonesia. Analisis faktor-faktor penyebab pengangguran di Sumatera menggunakan model regresi data panel menjadi tujuan dari penelitian ini. Hasil dari regresi data panel menunjukkan bahwa variabel upah minimum sebuah wilayah memiliki pengaruh positif terhadap pengangguran di Sumatera, variable pertumbuhan ekonomi atau peningkatan nilai barang dan jasa memiliki pengaruh negatif dengan pengangguran di Sumatera, dan variabel jumlah penduduk berpengaruh positif terhadap pengangguran di Sumatera. Tingginya angka pengangguran di sebuah negara akan menimbulkan banyak permasalahan antara lain meningkatkan kriminalitas sehingga membutuhkan perhatian dari pemerintah guna membekali tingginya jumlah penduduk dengan penyuluhan, pendidikan, pembinaan dan pelatihan kerja untuk meningkatkan produktivitas masyarakat.